2010
DOI: 10.1002/adfm.200902063
|View full text |Cite
|
Sign up to set email alerts
|

Template‐Directed Liquid ALD Growth of TiO2 Nanotube Arrays: Properties and Potential in Photovoltaic Devices

Abstract: Dense and well‐aligned arrays of TiO2 nanotubes extending from various substrates are successfully fabricated via a new liquid‐phase atomic layer deposition (LALD) in nanoporous anodic alumina (AAO) templates followed by alumina dissolution. The facile and versatile process circumvents the need for vacuum conditions critical in traditional gas‐phase ALD and yet confers ALD‐like deposition rates of 1.6–2.2 Å cycle−1, rendering smooth conformal nanotube walls that surpass those achievable by sol–gel and Ti‐anodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
94
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(97 citation statements)
references
References 36 publications
2
94
0
1
Order By: Relevance
“…The SEM micrographs in Fig. 4 show an advanced multilayered nested nanotube structure within the pores of the Si template composed of a sequence of TiO 2 and Pt nanotubes (two in series), which has potential applications in photovoltaic devices [21]. TiO 2 layers were grown with titanium isopropoxide (Ti( i PrO) 4 ) and H 2 O at 250 °C [8].…”
mentioning
confidence: 99%
“…The SEM micrographs in Fig. 4 show an advanced multilayered nested nanotube structure within the pores of the Si template composed of a sequence of TiO 2 and Pt nanotubes (two in series), which has potential applications in photovoltaic devices [21]. TiO 2 layers were grown with titanium isopropoxide (Ti( i PrO) 4 ) and H 2 O at 250 °C [8].…”
mentioning
confidence: 99%
“…These products have been utilized in a variety of promising applications such as magnetic recording media [916, 33, 34], thermoelectric materials [17, 18], optical materials [20–22, 48, 49], sensors [2325, 35], energy storage [25, 26, 36, 37, 50], photocatalysis [27, 51, 52], photovoltaic devices [28, 29] and biomaterials [5356]. …”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have reported that one-dimensional (1D) nanostructures [3][4][5][6][7][8][9][10] can be used in DSSCs in place of nanoparticles to facilitate the electron transferring. In addition to the unique electron properties, the 1D TiO 2 nanostructures have another function as light scattering materials with minimum sacrifice of the surface areas.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the unique electron properties, the 1D TiO 2 nanostructures have another function as light scattering materials with minimum sacrifice of the surface areas. The 1D TiO 2 nanostructures can either be fabricated perpendicular to the transparent electrode substrate [3][4][5][6][7] or randomly distributed during fabricating the TiO 2 photoanode based on nanoparticles [8][9][10]. Although the ordered TiO 2 nanostructures perpendicular to substrates can be more helpful for electron transport, the fabrication of these nanostructures in large area is still practically challenging.…”
Section: Introductionmentioning
confidence: 99%